Validation of a Satisfaction Questionnaire on Spa Tourism - Anaya-Aguilar, Rosa María; Gemar-Castillo, Germán; Anaya-Aguilar, Carmen (MDPI, 2021)
The authors’ line of research is within the existing methodological debate around the concepts of quality of services, destinations, and quality measurements methods. The authors consider that the most appropriate way to measure quality is to develop instruments according to the destination and context in question, defining the quality of the tourist destination for practical purposes based on the satisfaction experienced by the tourist or the SERVPERF model, weighted and used to measure the quality of sun and beach tourist destinations. The authors of this work propose the knowledge of spa tourism, its quality and its level of satisfaction as a research gap and consider it as a starting point to validate a questionnaire that would allow the measurement and comparison of parameters with other segments already studied and that can also serve as a measuring instrument for tourist segments with similar characteristics, not as well known in the international literature as inland, ecological or nature tourism. Good internal reliability results were obtained in all items and in all dimensions. The factor analysis distributed the weights of the variables in the theoretical model, and construct validity was obtained with an association between the global evaluation by dimension and the general significance. The score of the main questionnaire was statistically significant
Keywords: Viajes - Aspectos sanitarios; Spas; Satisfaction; Tourism; Health; Factor analysis